Phospholipase Dα1 Acts as a Negative Regulator of High Mg2+-Induced Leaf Senescence in Arabidopsis - Kocourková, Daniela; Kroumanová, Kristýna; Podmanická, Tereza; Daněk, Michal; Martinec, Jan (Frontiers in Plant Science, 2021)
Magnesium (Mg2+) is a macronutrient involved in essential cellular processes. Its deficiency or excess is a stress factor for plants, seriously affecting their growth and development and therefore, its accurate regulation is essential. Recently, we discovered that phospholipase Dα1 (PLDα1) activity is vital in the stress response to high-magnesium conditions in Arabidopsis roots. This study shows that PLDα1 acts as a negative regulator of high-Mg2+-induced leaf senescence in Arabidopsis. The level of phosphatidic acid produced by PLDα1 and the amount of PLDα1 in the leaves increase in plants treated with high Mg2+. A knockout mutant of PLDα1 (plda1-1), exhibits premature leaf senescence under high-Mg2+ conditions. In pldα1-1 plants, higher accumulation of abscisic and jasmonic acid and impaired magnesium, potassium and phosphate homeostasis were observed under high-Mg2+ conditions. High Mg2+ also led to an increase of starch and proline content in Arabidopsis plants. While the starch content was higher in plda1-1 plants, proline content was significantly lower in plda1-1 compared with wild type plants. Our results show that PLDα1 is essential for Arabidopsis plants to cope with the pleiotropic effects of high-Mg2+ stress and delay the leaf senescence.